Catastrophic health expenditure: a comparative analysis of empty-nest and non-empty-nest households with seniors in Shandong, China - Yang, Tingting (BMJ Open, 2016)
OBJECTIVE: The aim of this study was to compare the catastrophic health expenditure (CHE) prevalence and its determinants between empty-nest and non-empty-nest elderly households. SETTING: Shandong province of China. PARTICIPANTS: A total of 2761 elderly households are included in the analysis. RESULTS: CHE incidence among elderly households was 44.9%. The CHE incidence of empty-nest singles (59.3%, p=0.000, OR=3.19) and empty-nest couples (52.9%, p=0.000, OR=2.45) are both statistically higher than that of non-empty-nest elderly households (31.4%). An inverse association was observed between CHE incidence and income level in all elderly household types. Factors including 1 or more household elderly members with non-communicable chronic diseases in the past 6 months, 1 or more elderly household members being hospitalised in the past year and lower household income, are significant risk factors for CHE in all 3 household types (p<0.05). Health insurance status was found to be a significant determinant of CHE among empty-nest singles and non-empty-nest households (p<0.05). CONCLUSIONS: CHE incidence among elderly households is high in China. Empty-nest households are at higher risk for CHE than non-empty-nest households. Based on these findings, we suggest that special insurance be developed to broaden the coverage of health services and heighten the reimbursement rate for empty-nest elderly in the existing health insurance schemes. Financial and social protection interventions are also essential for identified at-risk subgroups among different types of elderly households.